PEMANFAATAN MEDIA WESITE WIZER.ME BERBANTUAN CANVA PADA TEKS FABEL DALAM PELAJARAN BAHASA INDONESIA - Pertiwi, Dora Hatika; Nurhamidah, Didah (Balai Bahasa Sumatera Utara, 2023)
This research aims to determine the use of learning media on the Wizer.me website assisted by Canva in Indonesian Fable Text lessons. The method used in this research is descriptive qualitative. The data source in this research is class VIII B students of SMP IP Yakin Jakarta located in Cengkareng, West Jakarta. This research instrument uses field observations. In collecting data using the Wizer.me website which has been modified using the Canva application link to be applied to class VIII B students in class and a questionnaire in the form of a Google form. The technique used in the research is a note-taking technique by describing the scores for each aspect. The assessment score uses a Likert scale. The use of Wizer.me media with the help of Canva is quite effective as a student worksheet on fable texts in Indonesian language lessons. The results of research on class VIII B students at SMP IP Yakin Jakarta showed that 75.9% of students liked the Wizer.me learning media, 79.3% students chose Wizer.me media as suitable for Fable Text material, 72.4% of students agreed that the learning material was suitable for Wizer.me Student Worksheets, 72.4% of students were interested in Wizer.me media as worksheets rather than paper, 72.4% students agree that the Wizer.me learning media assisted by Canva makes them easier to access Fable Text material, and 65.5% of students.